Hubungan Antara Usia dan Pengetahuan dengan Persepsi Stigma HIV/AIDS Pada Ibu Rumah Tangga di Kabupaten Garut - Hartiah Haroen; Wahyuni Maria Prasetyo Hutomo; Citra Windani Mambangsari; Witdiawati Witdiawati; Hasniatisari Harun (Malahayati Nursing Journal, 2024)
ABSTRACT There are approximately 5,100 new Human Immunodeficiency Virus (HIV) infections in the Housewife (IRT) group every year, and 35% of them are infected from their partners. This rate is higher than HIV cases in other groups such as the MSM (man sex with man). West Java is one of the four provinces with the highest number of HIV/AIDS cases in Indonesia. One of the districts in West Java with a high rate of HIV transmission is Garut Regency, where the estimation of 1,681 people with HIV/AIDS. To determine the relationship between age and knowledge with the perception of HIV/AIDS stigma among housewives. This research is a quantitative research with a cross sectional approach. Data collection was conducted in May 2023 and located in Village X, Garut Regency, West Java. The study population was housewives with inclusion criteria of women of childbearing age (aged 20-49 years) who resided permanently in the ciwalen sub-district area using purposive sampling technique as many as 97 housewives. Data collection was conducted door to door using a questionnaire which included demographic characteristics data, knowledge about HIV/AIDS using the HIV-KQ-18 Instrument consisting of 18 question items and perceived stigma using the stigma questionnaire from Berger's HIV Stigma Scale (HSS). Data were analyzed using SPSS software (Version 21), frequency distribution analysis and chi-square test. The research results showed that the majority of housewives (64 people, 66.0%) had poor knowledge about HIV, (32.0%) had high stigma about HIV and (34.0%) had low stigma. Meanwhile, only a few (34.0%) of the housewives had good knowledge and (25.8%) the housewives' stigma about HIV was low. Relationship between domestic workers' knowledge and stigma about HIV (P0.021). The majority of housewives in the early adulthood stage (55 people, 56.7%), had high stigma (28.9%) and low stigma (27.8%), low stigma was more often found in late adulthood housewives (53.4%). Age was related to stigma about HIV (P 0.014). To increase knowledge about HIV and reduce stigma in society, efforts are being made to increase knowledge and group discussions about HIV/AIDS. Keywords: HIV/AIDS, Housewives, Age, Knowledge, Stigma.  ABSTRAK Terdapat 5.100 infeksi Human Immunodeficiency Virus (HIV) baru  pada kelompok Ibu Rumah Tangga (IRT) setiap tahunya dan sebagian besar 35% tertular dari pasangannya, angkat tersebut lebih tinggi dibandingkan kasus HIV pada kelompok lainnya seperti kelompok MSM (man sex with man). Jawa Barat merupakan salah satu dari empat provinsi dengan jumlah kasus HIV/AIDS tertinggi di Indonesia. Salah satu kabupaten di Jawa Barat yang  angka penularan HIV-nya tinggi adalah Kabupaten Garut,  perkiraan jumlah orang yang hidup dengan HIV (ODHIV) sebanyak 1.681 orang. Diketahui hubungan usia dan pengetahuan dengan persepsi stigma  HIV/AIDS pada ibu rumah tangga. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan cross sectional. Pengambilan data dilakukan pada bulan Mei 2023 dan berlokasi di Desa X, Kabupaten Garut, Jawa Barat. Populasi penelitian adalah ibu rumah tangga dengan kriteria inklusi wanita usia subur (usia 20-49 tahun) yang bertempat tinggal tetap di wilayah tersebut dengan menggunakan teknik purposive sampling sebanyak 97 ibu rumah tangga. Pengumpulan data dilakukan secara door to door dengan menggunakan kuesioner yang meliputi data karakteristik demografi, pengetahuan tentang HIV/AIDS dengan menggunakan Instrumen HIV-KQ-18 yang terdiri dari 18 item pertanyaan dan stigma yang dirasakan dengan menggunakan kuesioner stigma dari Berger's HIV Stigma Scale (HSS). Analisis data dilakukan dengan menggunakan perangkat lunak SPSS (Versi 21), analisis distribusi frekuensi dan uji chi-square. Penelitian menunjukan mayoritas IRT (64 orang, 66,0%) memiliki pengetahuan yang kurang baik tentang HIV, (32.0%) memiliki stigma tentang HIV yang tinggi dan (34,0%) yang memiliki Stigma rendah. Sementara hanya sedikit (34,0%) diantara IRT yang memiliki pengetahuan baik dan (25,8%) stigma IRT tentang HIV yang rendah. Hubungan pengetahuan dan stigma IRT tentang HIV (P0.021). Mayoritas Usia IRT pada tahap dewasa awal (55 orang, 56.7%), memiliki  stigma tinggi (28,9%) dan stigma rendah( 27,8%), stigma rendah lebih banyak dijumpai pada IRT Usia dewasa akhir (53,4%). Usia memiliki hubungan dengan stigma tentang HIV (P 0.014). Untuk meningkatkan pengetahuan tentang HIV dan mengurangi stigma di masyarakat  dilakukan upaya-upaya peningkatan pengetahuan dan  diskusi kelompok bersama tentang HIV/ AIDS. Kata Kunci: HIV/AIDS, Ibu Rumah Tangga, Usia, Pengetahuan, Stigma.